The Influence of Organizational Commitment and Job Satisfaction on Turnover Intention (Case Study at Tunas Unggul Global Interactive School Bandung) - Regina Nursabrina W P; Mochamad Anjar Albagja (Politeknik Mardira Indonesia, 2024)
There are several conflicts, particularly regarding the turnover rate at Tunas Unggul Global Interactive School Bandung, which experiences an annual increase, especially in 2019 with a rate exceeding 75%. The increase is suspected to be due to various factors, including job dissatisfaction related to incentives, excessive workloads leading to overtime, a high desire to become a civil servant, and a lack of organizational commitment. Contributing factors may include handling company issues and the perception that the received compensation is inadequate compared to the amount of work and overtime performed. The objective of this research is to determine and analyze the influence of organizational commitment and job satisfaction on teacher turnover intention at Tunas Unggul Global Interactive School, both simultaneously and partially. The research method employed is a quantitative approach with a survey method, analyzed in a verificative and descriptive manner. The research results indicate a significant negative influence between organizational commitment and job satisfaction on turnover intention, both partially and simultaneously.